Combination of AES (Advanced Encryption Standard) and SHA256 Algorithms for Data Security in Bill Payment Applications - Rais Rabtsani, Muhamad; Triayudi, Agung; Soepriyono, Gatot (SAGA: Journal of Technology and Information System, 2024)
In the era of information technology development, digital payments and e-payments are becoming a dominant trend, supported by the crucial role of payment gateways such as Midtrans. Midtrans uses APIs to facilitate various online transactions, including debit cards. In this research, two cryptographic algorithms will be combined, namely Advance Encryption Standard (AES) with 256 bits and Secure Hash Algorithm (SHA) with 256 bits. The importance of data security in e-payments is recognized, with the application of cryptographic algorithms to protect sensitive transaction information. Yayasan Antero Prosesi Edukasi (YAPE) as an educational marketing consultant faced the challenge of time-consuming and inefficient manual payments. In an effort towards efficiency and security, YAPE plans to develop an online payment application with Midtrans Payment Gateway and the use of AES-256 and SHA-256 cryptographic algorithms. This step is expected to help the foundation keep up with technological developments, provide ease of payment, and achieve computerized efficiency. The results showed that the use of a combination of AES 256 bit and SHA256 encryption significantly increased security, making hacking attempts ineffective because encrypted data could not be accessed, with quite complicated calculation stages.